Dynamics of PKS Internal Cadre Nominations in the 2024 Bandar Lampung City Regional Elections: Dinamika Pencalonan Kader Internal PKS pada PILKADA Kota Bandar Lampung Tahun 2024 - Nur Islam; Eny Inti Suryani (Universitas Indo Global Mandiri, 2026)
Purpose: This study analyzes the nomination dynamics of internal cadres within the Prosperous Justice Party (PKS) and the factors shaping candidate decisions in the 2024 Bandar Lampung mayoral election. Design/Methodology/Approach: A qualitative case study approach was used. Data were collected through in-depth interviews, observation, and documentation with party officials, cadres, and political observers, then analyzed interactively using the Miles, Huberman, and Saldaña model, with triangulation applied to ensure validity and credibility. Findings: Candidate nomination follows a formal, hierarchical mechanism from local to central levels, yet remains shaped by informal dynamics and elite dominance. Internal factors—cadre loyalty, political capacity, and closeness to party elites—serve as initial considerations, while external factors—electability, coalitions, public pressure, and local political competition—become the primary determinants in final decisions, reflecting tension between cadre-based idealism and electoral pragmatism. Practical Implications: The study recommends that PKS strengthen a transparent, merit-based candidate selection system integrated with electoral considerations to balance cadre loyalty and electoral competitiveness. Originality/Value: This study offers novelty by examining internal cadre nomination dynamics at the local level, specifically in the Bandar Lampung mayoral election, highlighting the interplay of party structures, power relations, and external pressures, and contributing an institutional-rational framework to candidate selection analysis in cadre-based parties. Article Type: Research Paper